Outcome Worse for Women who Experience Myocardial Infarction Before Age 50 Years - Cheragh Hussain, Muhammad Hussain Afridi, Akbar Shah, Shaista Kawanl, Nizamuddin, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: From January 2019 to January 2020, the Department of Cardiology at Hayatabad Medical Complex conducted an analysis of 100 patients to discover the likelihood of a poorer outcome for women who have a myocardial infarction (MI) prior to reaching the age of 50. Calculations show that the prevalence of MI in the female population below the age of 50 amounts to 5.7%. Among patients aged 50 and under, females had a 27% higher rate of complications or death due to MI, such as arrhythmias, persistent angina, shock, and need for revascularization, when compared to males, who had only a 7% rate. The study suggests that women who suffer from myocardial infarction before age 50 have a more unfavorable outcome than their male counterparts who experience a similar event at the same age. The study likewise proposed additional prospective research to verify and reinforce its findings. Objectives: In patients under 50 years old, the effects of a heart attack were studied, with a focus on women. Male patients in this age range were also evaluated to compare outcomes. The goal of the research was to examine the results of myocardial infarction (MI) between genders. Methods: From January 2019 to January 2020, the Department of Cardiology at Hayatabad Medical Complex in Peshawar conducted a 100-patient study, retrospectively. The primary outcome focused on the need for revascularization, persistent angina, arrhythmias, and shock, with medical charts being the source of patient data. By analyzing female patients below the age of 50, we calculated the prevalence of myocardial infarction while comparing the rate of death or any other associated complications between male and female patients of the same age range. Results: Among females under the age of 50, a 5.7% prevalence of MI exists. While males only experience a 7% rate of death or complications due to MI, younger females encounter a significantly higher rate of 27%. Conclusion: Before the age of 50, women with a myocardial infarction had a worse outcome compared to men facing a similar event. The study prompted the suggestion for more prospective studies to authenticate the results. Keyboards: Myocardial Infarction, Prevalence, Outcome, Causes, Women, Age 50.